The Relationship Between Peer Support and Mental Well-Being of Badminton Athletes - Benita Permatasari; Indra Safari; Aam Ali Rahman (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to examine the relationship between peer support and the mental well-being of badminton athletes at the Mutiarani Badminton School Club in Majalengka. The study employed a quantitative approach with a correlational design involving 20 athletes selected through total sampling. Data were collected using Likert-scale questionnaires measuring peer support and athletes’ mental well-being, supported by interviews with coaches and assistant coaches. Data analysis was conducted using descriptive statistics and the Pearson Product Moment correlation test. The findings revealed a significant positive correlation between peer support and athletes’ mental well-being (r = 0.742, p < 0.05), indicating a strong relationship. The coefficient of determination showed that peer support contributed 55% to athletes’ mental well-being. Interview results also indicated that social support among athletes enhanced motivation, self-confidence, emotional stability, and enthusiasm during training and competition. These findings imply that fostering positive peer relationships within sports environments is important for maintaining and improving athletes’ psychological well-being and performance.